Inactivation of Human Glucose 6-Phosphate Dehydrogenase g6pdh by Peroxyl Radicals Is Strongly Modulated by Its Substrate and Cofactor - Arenas-Salinas, F (Elsevier Inc., 2025)
Glucose 6-phosphate dehydrogenase (G6PDH) is the rate-limiting enzyme of the pentose phosphate pathway (PPP). This enzyme catalyzes the oxidation of glucose 6-phosphate (G6P) into 6-phosphogluconolactone with concomitant reduction of NADP+ to NADPH. Despite the link between the PPP and oxidative stress, the oxidation and consequences on the activity of the human G6PDH (hG6PDH) has not been investigated. In the present work we report the oxidative inactivation of hG6PDH mediated by peroxyl radicals (ROO•) generated by AAPH (2,2′-azobis(2-methylpropionamidine) dihydrochloride) thermolysis. hG6PDH (46.4 μM, monomers) was incubated at 37 °C with 10 or 100 mM AAPH. At defined times, enzyme activity was determined (NADPH release followed at 340 nm), mapping of modifications studied by LC-MS, structural changes analyzed by circular dichroism, and results rationalized by in silico analysis of the three-dimensional structure of the enzyme. Analogous experiments were developed in the presence of NADP+ or G6P at excess or 1:1 (hG6PDH:NADP+ or G6P) molar ratios. High susceptibility to inactivation by ROO• was observed, 3.6 mol of ROO• inactivated 1 mol of hG6PDH. This behavior is rationalized, at least in part, by oxidation at Trp349 which is located close to the structural site of NADP+. The presence of G6P significantly increased the ROO•-mediated inactivation of hG6PDH, while an opposite effect was observed in the presence of NADP+ where, despite oxidation at different sites, the enzyme activity was practically unaltered by ROO•. These results demonstrate that hG6PDH is highly susceptible to inactivation mediated by ROO• with these processes strongly modulated by G6P and NADP+. © 2025 Elsevier Inc.